2009
DOI: 10.1111/j.1468-8123.2009.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of gas permeability and diffusivity of tight reservoir rocks: different approaches and their applications

Abstract: Permeability and diffusivity are critical parameters of tight reservoir rocks that determine their viability for commercial development. Current methods for measuring permeability and ⁄ or diffusivity may lead to erroneous results when applied to very tight rocks including gas shales, coal, and tight gas sands, as well as rocks considered as seals for nuclear waste repositories and strata for geological sequestration of CO 2 . The use of He as routinely applied to measure porosity, permeability, and diffusivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
382
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 640 publications
(390 citation statements)
references
References 36 publications
4
382
0
4
Order By: Relevance
“…Abundant studies have focused on CH 4 adsorption in organic matters of shale, and the results have revealed a positive correlation between the organic content and the CH 4 adsorption capacity in raw shale samples (Cui et al, 2009;Lu et al, 1995). The mechanism of CH 4 adsorption in organic matters has been well documented, illustrating that the surface functional groups and micropores provided the adsorption sites for CH 4 (Loucks et al, 2009;Ross and Bustin, 2007Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abundant studies have focused on CH 4 adsorption in organic matters of shale, and the results have revealed a positive correlation between the organic content and the CH 4 adsorption capacity in raw shale samples (Cui et al, 2009;Lu et al, 1995). The mechanism of CH 4 adsorption in organic matters has been well documented, illustrating that the surface functional groups and micropores provided the adsorption sites for CH 4 (Loucks et al, 2009;Ross and Bustin, 2007Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Pressures and temperatures were proposed to be the main factors that influence CH 4 adsorption and CH 4 reservoir (Cheng and Huang, 2004;Cui et al, 2009;Lu et al, 1995;Ross and Bustin, 2009). The experimental evaluation showed that the CH 4 adsorption capacity of shale increases with the increment of pressure (Cheng and Huang, 2004;Loucks et al, 2009;Lu et al, 1995;Bustin, 2007, 2008), implying that the high pressures in the actual shale gas reservoir might result in a large CH 4 adsorption amount.…”
Section: Introductionmentioning
confidence: 99%
“…This was done primarily to avoid the potentially significant effects of adsorption and/or associated swelling that might impact permeability [17][18][19]. Sample preparation included cutting, grinding, drying, and prestressing.…”
Section: Xperimentalmethodologymentioning
confidence: 99%
“…Here, first of all, modern infrared methods of measuring temperature [5][6][7], hydraulic ones -gas perme ability [8], capacitive -densities [9], eddy current -sand burning [10]. Structural [11] and intellectual [12] identi fiers and much more are used for obtaining information about the casting process.…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%